A numerical tidal stream energy assessment study for Baía de Todos os Santos, Brazil. (July 2017) - Marta-Almeida, Martinho; Cirano, Mauro; Guedes Soares, Carlos; Lessa, Guilherme C.
Abstract: Estuaries may have ideal technical conditions for tidal energy conversion: strong currents and proximity to the coast and urban/industrial infrastructures. This is the case of the estuary Baía de Todos os Santos, for which a numerical tidal potential density assessment was done. This study used a high resolution numerical configuration of the ocean model ROMS forced with realistic surface and lateral forcing, as well as with tides and river discharges into the bay. Strong currents were found along the main axis of the bay, particularly at the centre and left side of the bay's main entrance, and for a considerable time fraction. In these regions, speeds higher than 1 m s −1 were found during about 30% of the time leading to a power density around 1300 W m −2  at the surface layer, reaching peaks higher than 2500 W m −2 . The energetic flow at the left side of the inlet is affected by a remarkable sand ridge, the St. Antonio Bank, which intensifies the flow between the shoal and the coast. Operation time versus tidal power (OTP) diagrams for the bay's entrance show that even with a sharp reduction of operation time (50%) it is still possible to extract a high portion (95%) of the total power density available. Using tidally filtered time series of speed and power density, three important oscillations were found: fortnight associated with M2 +S2 spring-neap cycle; semi-annual caused by the S2 +K2 interference and responsible for about 1/4th of the total power density; and annual oscillation related with external forcings. The residual flow contributes substantially to the total power density. This contribution is however highly spatially variable, reaching at the bay's entrance 33% and 17% at the isobaths 10 and 25 m, respectively (at sites separated 2.5 km). Besides the bay's entrance, some regions inside the bay were identified as potentially interesting for tidal stream energy, but its study requires observations and also additional developments in the modelling configuration. Highlights: Tidal stream assessment was done for Baía de todos os Santos using model ROMS. The modelling configuration is the first for the region using realistic lateral and surface forcing. Strong currents were found at the bay's main entrance with power density reaching 2500 W m −2 . Residual and sub-tidal flow is responsible for a large portion of the extractable stream energy in the region.